Kinerja Bisnis UMKM: Peran Adaptasi Bisnis Dalam Memediasi Orientasi Kewirausahaan Dan Inovasi Produk - Meitiana; Kristinae, Vivy; Novan (Bahtera Inovasi, 2024)
This study aims to determine the Role of Business Adaptation in Mediating the Effect of Entrepreneurial Orientation and Product Innovation on the Business Performance of MSMEs in Palangka Raya. This research uses explanatory research with a quantitative approach. The sample in this study consists of 100 respondents. The analysis technique used is Partial Least Square (PLS). The results of the study indicate that: 1) Entrepreneurial Orientation has a positive and significant effect on Business Adaptation, 2) Product Innovation has a positive and significant effect on Business Adaptation, 3) Entrepreneurial Orientation has a positive and significant effect on Business Performance, 4) Product Innovation has a positive and significant effect on Business Performance, 5) Business Adaptation has a negative and significant effect on Business Performance, 6) Business Adaptation plays a negative and significant role in mediating the relationship between Entrepreneurial Orientation and Business Performance, and 7) Business Adaptation plays a negative and significant role in mediating the relationship between Product Innovation and Business Performance. It is recommended for future research to examine other factors influencing the business performance of MSMEs in Palangka Raya, such as internal company factors, external factors, and business environment factors.